Benign Regulation of the Astrocytic Phospholipase A2-Arachidonic Acid Pathway: The Underlying Mechanism of the Beneficial Effects of Manual Acupuncture on CBF - Ding, Ning; Jiang, Jing; Tian, Huiling; Wang, Shun; Li, Zhigang (Frontiers in Neuroscience, 2020)
Background: The astrocytic phospholipase A2 (PLA2)-arachidonic acid (AA) pathway is crucial in understanding the reduction of cerebral blood flow (CBF) prior to cognitive deterioration. In complementary and alternative medicine, manual acupuncture (MA) is used as one of the most important therapies for Alzheimer’s disease (AD). The beneficial effects of MA on CBF were reported in our previous study. However, the underlying molecular mechanism remains largely elusive. Objective: To investigate the effect of MA on the astrocytic PLA2-AA pathway in SAMP8 mice hippocampi. Methods: SAMP8 mice were divided into the SAMP8 control (Pc) group, the SAMP8 MA (Pm) group and the SAMP8 donepezil (Pd) group. SAMR1 mice were used as the SAMRl control (Rc) group. Mice in the Pd group were treated with donepezil hydrochloride at 0.65 μg/g. In the Pm group, MA was applied at Baihui (GV20) and Yintang (GV29) for 20 min. The above treatments were administered once a day for 26 consecutive days. The Morris water maze was applied to assess spatial learning and memory. Immunofluorescence staining, western blot and liquid chromatography-tandem mass spectrometry were used to investigate the expression of related proteins and measure the contents of the metabolic intermediates of the PLA2-AA pathway. Results: Compared with that in the Rc group, the escape latency in the Pc group significantly increased (p < 0.01); whereas, the platform crossover number and percentage of time and swimming distance in the platform quadrant decreased (p < 0.01). The hippocampal expression of PLA2, cyclooxygenase-1, cytochrome P450 proteins 2C23 and the levels of AA, prostaglandin E2 and epoxyeicosatrienoic acids of the Pc group was drastically higher than that in the Rc group (p < 0.01). These changes were reversed by MA and donepezil (p < 0.01 or p < 0.05). Conclusion: MA can effectively improve the learning and memory abilities of SAMP8 mice and has a negative regulatory effect on the PLA2-AA pathway. We propose that the increase of the arterial tone, which is induced by the inhibition of vasodilatory pathway, may be a reason for the beneficial effect of MA on CBF.